Defluoridation of Drinking Water Using Calcium Modified Chitosan - Chakraborty, Meena; Pandey, Madhurima; Pandey, Piyush Kant (Asian Journal of Chemistry, 2016)
Fluoride in water has become a major environmental and health issue now a day. A new adsorbent chitosan calcium compound was prepared and used for defluoridation purpose. Defluoridation capacity of the adsorbent was studied by batch technique. Adsorption of fluoride was studied as a function of contact time, pH, initial fluoride concentration and adsorbent dose. The equilibrium sorption data were fitted to Freundlich, Langmuir and Temkin isotherms. The kinetics of sorption was found to follow pseudo second order and particle diffusion model. Result shows that the chitosan calcium adsorbent can be used for defluoridation of water without causing any harm to environment.